SISTEM PERTANIAN PADI LADANG DI DESA NGIDIHO KECAMATAN GALELA BARAT KABUPATEN HALMAHERA UTARA - Yusuf, Jusan; Abd Rahman , Safrudin (Universitas Hasanuddin, 2024)
This study was conducted to see the dryland rice production system in Ngidiho Village, West Galela District, North Halmahera Regency. The dryland rice production system in the Ngidiho community is still maintained to this day. This study illustrates that the dryland rice production system in Ngidiho Village is one of the main factors for the local community, this study also reveals that the Ngidiho community maintains the dryland rice system because of household economic needs and rituals. The method used in this study is descriptive qualitative by taking samples in the form of interview instruments proven by documentation. This method is used to analyze the development of the lives of the Ngidiho Village farming community and the uniqueness of work towards a productive community in farming.